1986
DOI: 10.1128/jb.165.3.771-779.1986
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of the Bacillus subtilis spoIID gene

Abstract: We cloned the wild-type allele of the spolID locus of Bacillus subtilis. This DNA region was shown to be transcribed beginning within an hour after the onset of sporulation. The amount of spoIID mRNA present in ceUs at 1 h after the end of growth was more than 50-fold greater than it was in growing cells; the pool of this mRNA decreased steadily after 1.5 h after the end of growth. spoIlD mRNA was present in stationary-phase cells of sporulation mutants with lesions in the spoOJ and spolIB genes but was absent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 32 publications
2
90
1
Order By: Relevance
“…We found that the GE156K protein accumulated starting 2 h after the onset of sporulation, reaching maximum levels around 3 h after sporulation had begun (Fig. 8B), which is in accordance with the temporal pattern of expression of a spoIID-lacZ fusion (36). In contrast, the wild-type form of G was detected only in trace amounts (Fig.…”
Section: Vol 186 2004 Regulation Of G 4005supporting
confidence: 59%
See 2 more Smart Citations
“…We found that the GE156K protein accumulated starting 2 h after the onset of sporulation, reaching maximum levels around 3 h after sporulation had begun (Fig. 8B), which is in accordance with the temporal pattern of expression of a spoIID-lacZ fusion (36). In contrast, the wild-type form of G was detected only in trace amounts (Fig.…”
Section: Vol 186 2004 Regulation Of G 4005supporting
confidence: 59%
“…7). In contrast, expression of the spoIIIGE156K allele promptly resulted in sspE-lacZ expression, which occurred prior to normal expression of sspE in the prespore, in agreement with the timing of utilization of the spoIID and sspE promoters during sporulation (26,36) (Fig. 7).…”
Section: Vol 186 2004 Regulation Of G 4005mentioning
confidence: 75%
See 1 more Smart Citation
“…Three loci have been identified in which mutations arrest sporulation at stage IIii: spoIID, spoIIM and spoIIP. These genes are all under the control of E and consequently their products are synthesized only in the mother cell (Rong et al, 1986;Driks and Losick, 1991;Frandsen and Stragier, 1995). The only available information on their role is provided by their sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Various deletions and disruptions were created in the immediate vicinity of the original fusion points. We checked the effect of these mutations on sporulation and (rE activity on solid media, by introducing them into a wild-type strain containing a fusion of lacZ to the (rE-controlled spolID promoter (Rong et al 1986). …”
Section: Londofo-vallejo and Stragiermentioning
confidence: 99%